Device-based physical activity measures for population surveillance—issues of selection bias and reactivity - Christiansen, Lars Breum; Koch, Sofie; Bauman, Adrian; Toftager, Mette; Bjørk Petersen, Christina; Schipperijn, Jasper (Frontiers in Sports and Active Living, 2023)
Background: Device-based measurement in physical activity surveillance is increasing, but research design choices could increase the risk of self-selection bias and reactive behaviour. The aim of this study is to compare the self-reported physical activity profiles of four different samples: participants in a large national survey, participants in a telephone-based survey of non-responders, participants in the large national survey who accepted the invitation to device-based measuring, and the same sample during the week of monitoring. Methods: In October 2020, 163,133 Danish adults participated in a national survey and of those 39,480 signed up for device-based measurements. A balanced random sample (n=3,750) was invited to wear an accelerometer of whom 1,525 accepted the invitation. Additionally, a short telephone-based survey on 829 non-responders to the national survey was conducted. Sociodemographic characteristics and self-reported weekly frequencies of physical activity across four domains are compared.The participants in the national survey were older, more often female, and more often not working. Participants in the telephone-based survey were younger, more often doing unskilled work, and were more often active at home and at work. The participants in the device-based sample were more often active during transport and leisure in the national survey, and participants categorized in the most active category increased during the week of monitoring from 29.0% to 60.7% and from 58.5% to 81.7% for active transport and leisure activities, respectively. Recruiting a population representative sample for device-based measurement of physical activity is challenging, and there is a substantial risk of sample selection bias and